A Multichannel Ca2+ Nanomodulator for Multilevel Mitochondrial Destruction‐Mediated Cancer Therapy. Issue 15 (6th March 2021) - Zheng, Pan; Ding, Binbin; Shi, Run; Jiang, Zhongyu; Xu, Weiguo; Li, Gao; Ding, Jianxun; Chen, Xuesi
Abstract: Subcellular organelle‐targeted nanoformulations for cancer theranostics are receiving increasing attention owing to their benefits of precise drug delivery, maximized therapeutic index, and reduced off‐target side effects. Herein, a multichannel calcium ion (Ca 2+ ) nanomodulator (CaNMCUR+CDDP ), i.e., a cisplatin (CDDP) and curcumin (CUR) co‐incorporating calcium carbonate (CaCO3 ) nanoparticle, is prepared by a facile one‐pot strategy in a sealed container with in situ synthesized polydopamine (PDA) as a template to enhance Ca 2+ ‐overload‐induced mitochondrial dysfunction in cancer therapy. After systemic administration, the PEGylated CaNMCUR+CDDP ( PEG CaNMCUR+CDDP ) selectively accumulates in tumor tissues, enters tumor cells, and induces multilevel destruction of mitochondria by the combined effects of burst Ca 2+ release, Ca 2+ efflux inhibition by CUR, and chemotherapeutic CDDP, thereby observably boosting mitochondria‐targeted tumor inhibition. Fluorescence imaging of CUR combined with photoacoustic imaging of PDA facilitates the visualization of the nanomodulator. The facile and practical design of this multichannel Ca 2+ nanomodulator will contribute to the development of multimodal bioimaging‐guided organelle‐targeted cancer therapy in the future. Abstract : A curcumin (CUR) and cisplatin (CDDP) co‐incorporating multichannel calcium‐ion (Ca 2+ ) nanomodulator ( PEG CaNMCUR+CDDP ) demonstrates enhanced anticancer efficacy owing to induced multilevel mitochondrial damage by Ca 2+ overload, which is promoted by the degradation of amorphous calcium carbonate, the CUR‐mediated Ca 2+ metabolism, and the CDDP‐augmented synergistic destruction of mitochondria, which can be visualized by both fluorescence and photoacoustic imaging.